Proliferation of Embryogenic Callus of Oil Palm (Elaeis guineensis Jacq.) Using Different Culture Systems and Genetic Instability Assay by Simple Sequence Repeat (SSR) Technique - Stapaporn Kerdsuwan (Science Faculty of Chiang Mai University, 2019)
Efficiency in propagation of embryogenic callus (EC) of oil palm was investigated using solid medium, liquid medium and temporary immersion system (TIS) to improve micropropagation.TIS was found to be suitable for EC proliferation. The EC immersed in 150 ml EC medium which was MS supplemented with 0.1 mg/L dicamba and 200 mg/L ascorbic acid and 3.75% sucrose containing in 500 mL Erlenmyer flask for 3 min followed by leaving it dry for 8 h gave the highest growth ratio at 11.19 folds of origin, significant different with another treatments. Analysis of genetic instability in EC raised on TIS system by SSR technique using 9 primers namely EgClR0008 EgClR0243 EgClR0337 EgClR0409 EgClR0446 EgClR0465 EgClR0781 EgClR0905 and EgClR1172 resulted in DNA patterns with monomorphism bands. All of the primers provided clear profile of DNA patterns and high uniformity without l variation of EC. The results obtained from this study suggest that there are no variations in cultured EC using TIS system.